A phase II of gemcitabine combined with pazopanib followed by pazopanib maintenance, as second-line treatment in patients with advanced leiomyosarcomas: A unicancer French Sarcoma Group study (LMS03 study). (January 2020) - Pautier, P.; Penel, N.; Ray-Coquard, I.; Italiano, A.; Bompas, E.; Delcambre, C.; Bay, J.-O.; Bertucci, F.; Delaye, J.; Chevreau, C.; Cupissol, D.; Bozec, L.; et al.
Abstract: Background: Options in second-line therapy after doxorubicin-based chemotherapy for metastatic/advanced leiomyosarcoma include gemcitabine (G), trabectedin and pazopanib (P) monotherapy. Currently, no combination therapy is better than monotherapy. LMS03 is an open-label multicentre single-group phase II study designed to assess the efficacy and tolerance of G + P in the second-line setting. Patients and methods: Patients (pts), ECOG ≤2, with metastatic leiomyosarcomas (LMS) after first-line doxorubicin chemotherapy failure were eligible. Pts were treated with G 1000 mg/m 2 on days 1 and 8 of each 21 days (maximum eight cycles), in combination with oral daily P (800 mg), until disease progression/toxicity. 9-month progression-free survival (PFS) rate was the primary endpoint. Inacceptable and promising 9-month PFS rates were defined, in the intent-to-treat population, as 32% and 44%. Results: 106 pts were included with a mean age of 59.8 years and an ECOG 0 in 63.5%; the primary tumour site was uterus in 61%. Pts were treated with P + G for a median of 3.8 mo, and P for a median of 4.2 mo. The 9-month PFS rate was 32.1% (95% CI 23.1–41.1). After a median follow-up of 14.2 months, the PFS was 6.5 months (95% CI 5.6–8.2), and the overall survival was 22.4 months (95% CI 16.9–26.5). The best response was 23.8%. The most frequent reported grade 3–4 adverse events were haematological. Conclusions: LMS03 failed to show that second-line therapy, with gemcitabine combined with pazopanib, followed by pazopanib alone, was beneficial for advanced LMS patients. Eudract N°2011-001308-36 and NCT01442662. Highlights: Gemcitabine combined with pazopanib in second-line leiomyosarcoma after doxorubicine failure is feasible without limiting toxicity. The 12-week disease control rate was 83.6%, and the best response during the treatment was 23.8%. The LMS03 study failed to meet its primary objective but is nearly positive when considering per-protocol results with a median PFS 7.1 months.